Insight from India on managing plastic waste - Gew, Lai Ti *; Long, Chiau Ming * (Star Media Group Berhad, 2023)
Malaysia is a major player in the global plastics sector with around 1,300 manufacturers located here. A report by market research company Mordor Intelligence states that the Malaysia plastics market size is estimated at US$3.74bil in 2023, and is expected to reach US$4.53bil by 2028.